Analyzing PHP Project - Medicare - Dharsan.R,; Krishanthini.M,; Traveena.C,; Anubama.L,; D. I. De Silva,; Thisuru.D, (International Journal of Engineering and Management Research, 2022)
This research paper is related to our software project which is known as Medicare hospital management system. In this research paper we have added the introduction for our project, related works, and methodology used proposed system and discussions. We have explained and proved how we did this project and how it will use in future as well. Related work topic, methodology, and proposed system topic has some subtopics such as Doctor Management, Patient management, medicine Inventory management, Laboratory management. At the discussion part we have summarized the whole content of the research paper.